التكييف القانوني للعلاقة بين المصرف والعميل في القانون السوداني والأعراف المصرفية (دراسة تحليله مقارنة) - محمد فضل الله, كمال الأمين (Gezira Journal of Educational Sciences and Humanities; مجلد 20 عدد 2 (2023), 2026)
تتثمل أهمية الدراسة في زيادة التقة بين المصرف والعميل في ظل القانون، وتحديد الحقوق والالتزامات بين العميل والمصرف، وذلك بتكييف العلاقة القانونية بين المصرف والعميل في القانون السوداني والأعراف المصرفية، وذلك  يقلل من النزاعات المصرفية بين الطرفين، تناولت الدراسة ماهية المصرف ونشأته وأنواعه، وماهية العلاقة بين المصرف والعميل والتكييف القانوني لها في القانون السوداني. هدفت الدراسة إلى عدة أهداف من بينها بيان التكييف القانوني للعلاقة بين المصرف والعميل في القانون السوداني، وتحليل دور العرف المصرفي كمصدر مكمل  للتشريع، وتقييم موقف القضاء السوداني من العلاقة بين العميل والمصرف،  واتبعت هذه  الدراسة المنهج الوصفي التحليلي والمنهج الاستقرائي والمقارن، وتتمثل مشكلة الدراسة في ما هو التكييف القانوني الصحيح للعلاقة بين المصرف والعميل في القانون السوداني، وكيف تسهم الأعراف المصرفية في سد النقص التشريعي،  وتوصلت الدراسة إلى عدة نتائج من أهمها أن التكييف القانوني  لعلاقة البنك  بالعميل في القانون السوداني فيما يتعلق بإيداع النقود والحسابات الجارية وحسابات الادخار والتوفير هي علاقة  قانونية تعاقدية وهى علاقة دائن بمدين، ويأخذ القضاء السوداني في حالة غياب النص بالأعراف المصرفية باعتبار العرف مكمل للتشريع، وخلصت الدراسة إلى عدة توصيات من أهمها دعوة المشرع السوداني إلى تقنين الأعراف المصرفية الأساسية باعتبار العرف مكمل للتشريع، وأن توحد المحاكم السودانية في اجتهادها القضائي بشأن التكييف القانوني للحسابات المصرفية. This study highlights the importance of enhancing trust between the bank and the customer within the framework of the law and defining the rights and obligations of both parties by determining the legal characterization of the relationship between the bank and the customer in Sudanese law and banking customs. This, in turn, contributes to reducing banking disputes between the two parties. The study addresses the concept of the bank, its origin and types, as well as the nature of the relationship between the bank and the customer and its legal characterization in Sudanese law. The study aims at several objectives, including clarifying the legal characterization of the relationship between the bank and the customer in Sudanese law, analyzing the role of banking custom as a supplementary source of legislation, and evaluating the position of the Sudanese judiciary regarding the relationship between the customer and the bank. The study adopts the descriptive-analytical method, the inductive method, and the comparative method. The research problem is represented in determining the correct legal characterization of the relationship between the bank and the customer in Sudanese law, and how banking customs play a role in filling legislative gaps. The study reached several findings, the most important of which is that the legal characterization of the relationship between the bank and the customer in Sudanese law, with regard to cash deposits, current accounts, and savings accounts, is a contractual legal relationship, namely a creditor–debtor relationship. The Sudanese judiciary, in the absence of a statutory provision, relies on banking customs as a supplementary source of legislation. The study concluded with several recommendations, the most important of which are calling upon the Sudanese legislator to codify the fundamental banking customs as a supplementary source of legislation, and urging the Sudanese courts to unify their judicial interpretation regarding the legal characterization of banking accounts.